Stroke prevention in Hispanic children with sickle cell anemia: the SACRED trial - Rosa M. Nieves; Teresa Latham; Nicolle Marte; Melissa Berges; Luisanna M. Sánchez; Gabriela Urcuyo; Carla Florencio; Carla Gonzalez; Paola del Villar; Sheena Chen; Daniel Ramirez; Paula Reyes; et al. (Blood Advances)
Abstract: Sickle cell anemia (SCA) is recognized globally, but little is known about affected Hispanic populations. In partnership with the Dominican Republic, a Hispanic Caribbean island with a large SCA population, a transcranial Doppler (TCD) screening program provided hydroxyurea to children with conditional velocities. Building local capacity, 10 Dominican medical graduates were certified in TCD examinations and trained in hydroxyurea management. The Stroke Avoidance for Children in REpública Dominicana (SACRED) trial enrolled 283 children with average age of 8.7 ± 3.4 years and 130 (46%) females. At initial screening, treatment-naïve children with conditional velocities (170-199 cm/s) were younger (6.6 ± 2.7 vs 8.9 ± 3.4 years; P = .0002) and more anemic (hemoglobin, 7.4 ± 0.8 vs 8.0 ± 1.2 g/dL; P = .0046) than children with normal screening velocities (<170 cm/s). Among 57 treatment-naïve children receiving 6 months of fixed-dose hydroxyurea at 20 mg/kg per day, average TCD velocities decreased by 20 cm/s, and 61% became normal. Compared with fixed-dose hydroxyurea, dose escalation to maximum tolerated dose (MTD) led to fewer sickle-related events with incidence rate ratio 0.59, 95% confidence intervals 0.36 to 0.98, P = .0420. At MTD, TCD benefits were sustained over 5 years, with 81% reverting to normal and an average TCD velocity decrease of 27 cm/s. Brain magnetic resonance imaging documented substantial baseline parenchymal disease; during treatment, 10% developed new vasculopathy, plus 1 stroke and 1 death. The SACRED trial documents a high burden of cerebrovascular disease among Hispanic children with SCA and demonstrates the feasibility of partnership to establish TCD screening programs, the utility of hydroxyurea to reduce TCD velocities and reduce stroke risk, and sustained benefits of hydroxyurea dose escalation. This trial was registered at www.clinicaltrials.gov as #NCT02769845.